Spatiotemporal evolution and clustering patterns of settlements from the Neolithic to the Bronze Age (9000–3000 BP) in the Songshan Mountain region, China - Lijie Yan; Xia Wang; Li Zhang; Fei Teng (PLoS ONE, 2026)
This study proposes a transparent and methodologically explicit GIS-based framework for delineating prehistoric settlement clusters and tracking their spatiotemporal evolution. Integrating nearest-neighbor analysis, kernel density estimation, least-cost path (LCP) modeling, and K-medoids clustering, we analyze 1,975 settlement sites from four successive cultural phases (Peiligang, Yangshao, Longshan, and Xia-Shang; 9000–3000 BP) in the Songshan Mountain region, a core area of early Chinese civilization. Results show persistent clustered distribution across all periods, with aggregation intensity peaking during the Xia-Shang period. High-density zones shifted progressively westward, and by the Xia-Shang period, a spatial pattern that appears consistent with a potential dual-core structure can be identified centered on Yanshi and Zhengzhou. K-medoids clustering reveals a marked reduction in optimal cluster numbers from nine to two despite a five-fold increase in site numbers. This trend is consistent with spatial integration and is suggestive of socio-political centralization. Environmental factors provided the primary context for settlement distribution from the Peiligang to Longshan period, but spatial patterns suggest socio-political factors may have exerted an important influence on aggregation during the Xia-Shang period even under deteriorating climate conditions. Our framework offers a replicable approach for analyzing settlement clustering and human-environment interactions.